Traditional fishing methods practiced by Ao and Sumi tribes in Dikhu River of Nagaland, India - Metevinu Kechu; Pranay Punj Pankaj (Journal of Fisheries, 2023)
Traditional fishing knowledge dates back to the early fish catching techniques passed down from forefathers in most of the Naga communities, Nagaland. Traditional fishing is mainly practiced for household consumption and is considered less intensive than industrial fishing practices, which can negatively impact riverine sustainability. However, there is a risk of loss of traditional knowledge in recent times. Hence, an effort was made to comprehend and document the indigenous traditional knowledge associated with fishing practices utilized by the Ao and Sumi tribal communities residing along the banks of Dikhu River. The diverse array of traditional fishing equipment and techniques employed has been categorised based on their specific functions, resulting in the documentation of three types of fishing gears, four fishing accessories, one fishing craft and three other types of fishing techniques. However, in some regions, use of detrimental fishing like dynamites and harsh chemicals were encountered. The results indicate that local fishers continue to rely on indigenous fishing practices for sustenance, and the majority of traditional fishing gears are constructed using locally available eco-friendly materials such as bamboo, wooden poles and cotton twine. The information obtained in this study can be preserved and implemented in contributing better resource management.